COOPERATION WITH INTERNATIONAL FINANCIAL INSTITUTIONS IN THE DEVELOPMENT OF THE BANK'S INVESTMENT ACTIVITIES - Khujumov Nurbek Obidjon ugli (American Journals, 2025)
The article analyzes the role and importance of cooperation with international financial institutions in the development of banks' investment activities. Credit lines, grants, and technical assistance from the World Bank, the Asian Development Bank, the European Bank for Reconstruction and Development, the International Finance Corporation, the Islamic Development Bank, and other financial institutions are considered an important source for increasing the stability of the banking system. The possibilities of attracting long-term resources to the banking sector through international cooperation, developing capital markets, introducing digital technologies, supporting small and medium-sized businesses, and expanding green finance mechanisms will also be substantiated. According to the research results, effective cooperation with international financial institutions strengthens the investment potential of banks and serves the sustainable development of the country's economy.
Keywords: Bank investment activity, international financial institutions, World Bank, Asian Development Bank, European Bank for Reconstruction and Development, International Finance Corporation (IFC), Islamic Development Bank, capital market, credit lines, small and medium-sized businesses, green finance, sustainable development, Basel standards.